Disaster Risk Financing and Insurance in Sub-Saharan Africa : Review and Options for Consideration - World Bank (Washington, DC, 2017)
This policy note is a preliminary effort to present a body of knowledge on the state of disaster risk financing and insurance in Sub-Saharan Africa. It aims to contribute to a strengthened understanding and collective knowledge within Sub-Saharan Africa on disaster risk financing and insurance, and to encourage open dialogue between stakeholders on how strategies can best be developed to increase financial resilience against natural disasters. The report is targeted at policy-makers and actors in the international community with an interest in this agenda. In the context of this report, disaster risk financing and insurance refers to instruments and mechanisms at the macro, market and micro level that provide financial resources to assist with response and recovery efforts in the aftermath of a disaster. This report focuses on natural disasters, which we can describe as unforeseen events driven by natural phenomena that cause serious disruption of the functioning of a community or a society causing widespread human, material, economic and/or environmental losses which overwhelm the capacity of the affected community or society. This report discusses rapid onset disasters such as cyclones, earthquakes and floods but also slow onset events such as drought. Sub-Saharan African countries are highly exposed to a wide range of adverse natural events, with hydro-meteorological hazards impacting the largest number of people. Disaster risk financing and insurance (DRFI) has been highlighted by the African union, regional economic communities and individual countries as an area for regional financial cooperation.